Increased urinary sodium excretion is associated with systolic blood pressure in first degree relatives of hypertensive patients in Ibadan, Southwestern Nigeria. (2018)
Introduction: Understanding the risk factors of hypertension has led to a better understanding of the pathogenesis, prevention and reduction in morbidity of hypertension. It is well known that offsprings of hypertensive parents have an increased risk of developing hypertension. It is therefore necessary to explore the physiological differences between normotensive patients with and without a positive family history of hypertension with respect to their urinary excretion of sodium. Methods: This study was carried out at the University College Hospital, Ibadan Nigeria, to determine if normotensive patients with a positive family history of hypertension are different with respect to their urinary excretion of electrolytes and blood pressure. It examined the relationship between 24-hour urinary excretion of sodium, chloride and potassium, urea and creatinine and blood pressure in subjects with and without family history of hypertension. It was a case-control study of sixty-two subjects: normotensive patients’ first degree relatives of primary hypertensive patients and normotensive patients without positive family history. Results: The mean (SD) systolic blood pressures for subjects with and without family history of hypertension were significantly different: 120.0(22.25) and 105.0(17.50) respectively, (p=0.001). The mean arterial blood pressures were significantly different: 86.4(10.2) mmHg and 80.1(8.1) mmHg respectively (p=0.010). The mean (SD) 24-hour urinary excretion of sodium for normotensive patients with and without positive family history of hypertension were 180.5 (45.50) mEq/L, and 156.0(36.25) mEq/L respectively. Systolic blood pressure and 24-hour urinary excretion of sodium was also higher in normotensive subjects with a positive family history of hypertension. Conclusion: Systolic blood pressure and twenty-four hour urinary excretion of sodium were higher in normotensive subjects with a positive family history of hypertension than in those without a family history of hypertension.